Adapting imaging protocols for PET-CT and PET-MRI for immunotherapy monitoring - Beuthien-Baumann, Bettina; Sachpekidis, Christos; Gnirs, Regula; Sedlaczek, Oliver (Cancers, 2021)
Hybrid imaging with positron emission tomography (PET) in combination with computer tomography (CT) is a well-established diagnostic tool in oncological staging and restaging. The combination of PET with magnetic resonance imaging (MRI) as a clinical scanner was introduced approximately 10 years ago. Although MRI provides superb soft tissue contrast and functional information without the radiation exposure of CT, PET-MRI is not as widely introduced in oncologic imaging as PET-CT. One reason for this hesitancy lies in the relatively long acquisition times for a PET-MRI scan, if the full diagnostic potential of MRI is exploited. In this review, we discuss the possible advantages of combined imaging protocols of PET-CT and PET-MRI, within the context of staging and restaging of patients under immunotherapy, in order to achieve “multi-hybrid imaging” in one single patient visit.
Gesehen am 08.06.2022